2020
DOI: 10.11591/ijeecs.v19.i3.pp1177-1185
|View full text |Cite
|
Sign up to set email alerts
|

ANFIS controller for vector control of three phase induction motor

Abstract: For variable speed drive applications such as electric vehicles, 3 phase induction motor is used and is controlled by fuzzy logic controllers. For the steady functioning of the vehicle drive, it is essential to generate required torque and speed during starting, coasting, free running, braking and reverse operating regions. The drive performance under these transient conditions are studied and presented. In the present paper, vector control technique is implemented using three fuzzy logic controllers. Separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…A vector controller alligned on the PW reference frame is proposed to change the speed and reactive power independently [24]. The reactive power and speed are calculated analytically using the mathematical model of BDFIM while the PI controller gains are derived through the IMC method.…”
Section: Proposed Imc Based Vc Schemementioning
confidence: 99%
“…A vector controller alligned on the PW reference frame is proposed to change the speed and reactive power independently [24]. The reactive power and speed are calculated analytically using the mathematical model of BDFIM while the PI controller gains are derived through the IMC method.…”
Section: Proposed Imc Based Vc Schemementioning
confidence: 99%
“…A vector controller oriented on the PW reference frame is proposed to regulate the speed and reactive power independently [20]. The reactive power and speed are calculated analytically using the mathematical model of BDFIM while the PI controller gains are derived through the IMC method [21].…”
Section: Proposed Control Techniquementioning
confidence: 99%
“…Another study reported the impacts of motor and simulated motors, which were examined using motor current signature analysis (MCSA) and also through observation of magnetic flux density outside the motor [11]. Different approaches have been adopted to control the [4,[12][13][14][15] these approaches are explained below. Several experimental outcomes were provided to showing the impact of bearing and armature faults in single-phase induction motor [16].…”
Section: Introductionmentioning
confidence: 99%